(untitled) (Altre Modernità, 2014)
In the Medieval Hebrew Literature, we have no evidence about women as authors, except for Dunash ibn Labrat’s wife (X cent.) and Qasmuna bat Isma’il (XII cent.). Women were not "silent" at all in the Middle Ages, but the feminine way to compose texts at that time was oral, being made in the native Jewish-Languages, while Hebrew – known almost only by men - was the language of the written Literature. In this essay we will deal with the (self-)representation of women in the Judaeo-Provencal medieval literary corpus. First, we will analyze some texts, explicitly composed for women, in order to understand the feminine perspective and literary liking as a public. Second, we will deal with an example of women literary creativeness, i.e. a particular Jewish blessing, transmitted in three extant Jewish prayerbooks (XV century), which recites: “Bless you God, for I was born a woman”. This probably refers to a local tradition of Provencal Jewish women who created it during the Middle Ages.